Adaptation of water resources systems to changing society and environment: a statement by the International Association of Hydrological Sciences. Issue 16 (9th December 2016) - Ceola, Serena; Montanari, Alberto; Krueger, Tobias; Dyer, Fiona; Kreibich, Heidi; Westerberg, Ida; Carr, Gemma; Cudennec, Christophe; Elshorbagy, Amin; Savenije, Hubert; Van Der Zaag, Pieter; Rosbjerg, Dan; et al.
ABSTRACT: We explore how to address the challenges of adaptation of water resources systems under changing conditions by supporting flexible, resilient and low-regret solutions, coupled with on-going monitoring and evaluation. This will require improved understanding of the linkages between biophysical and social aspects in order to better anticipate the possible future co-evolution of water systems and society. We also present a call to enhance the dialogue and foster the actions of governments, the international scientific community, research funding agencies and additional stakeholders in order to develop effective solutions to support water resources systems adaptation. Finally, we call the scientific community to a renewed and unified effort to deliver an innovative message to stakeholders. Water science is essential to resolve the water crisis, but the effectiveness of solutions depends, inter alia, on the capability of scientists to deliver a new, coherent and technical vision for the future development of water systems.EDITOR D. Koutsoyiannis;ASSOCIATE EDITOR not assigned